Influence of Tropical Fruit Beverages on Color Stability and Roughness of Resin Composites - Ana Carolina Freitas Ribeiro; Fabiana Mantovani Gomes França; Flávia Lucisano Botelho do Amaral; Cecília Pedroso Turssi; Roberta Tarkany Basting; Waldemir Francisco Vieira-Junior (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate the effects of Amazonian tropical fruit juices on the color and surface roughness of resin composites. Material and Methods: Cylindrical specimens (Ø6 × 2 mm) of microhybrid (Filtek Z250XT) and nanofilled (Filtek Z350XT) resin composites were subjected to roughness (µm, Ra) and color analyses (CIE L*a*b*, CIEDE2000 and Vita Scale). The analyses were performed at baseline and after 7 days of immersion in the solutions (n=12): distilled water (control), açaí beverage (Euterpe oleracea), bacuri beverage (Platonia insignis), or muruci beverage (Byrsonima crassifolia). The data were evaluated using the Kruskal-Wallis, Dunn, Mann-Whitney, and Wilcoxon tests (α=0.05). Results: The bacuri increased the Ra of the nanofilled resin composite (p=0.0284). The nanofilled resin composite obtained higher ΔEab and ΔE00 values compared with the microhybrid resin composite, regardless of the beverage (p<0.01). Exposure to açaí or muruci beverages increased the b* values (p<0.0001), altered a* values (p=0.0051), and promoted higher ΔEab and ΔE00 values than the control (p<0.0001). Both resin composites showed higher Vita scale scores when exposed to muruci and açaí beverages (p=0.0051). Conclusion: Tropical beverages can negatively influence the color stability of resin composites. The greatest changes in resin composite color were detected from muruci and açai beverages, and these effects were greater in the nanofilled resin composite.